What is community justice? case studies of restorative justice and community supervision - Karp, David R. 1964-; Clear, Todd R. (Thousand Oaks, Calif. London Pine Forge, 2002)
As described in this title, the aim of the new efforts is to explicitly integrate the community and the criminal justice process in probation programs. There are five goals that this text addresses to achieve this end.
Keywords: Community-based corrections -- United States; Restorative justice -- United States